Modelo AC para el despacho combinado de contratos bilaterales y bolsa de energía considerando restricciones de seguridad - López-Lezama, Jesús María; Granada-Echeverri, Mauricio; Gallego-Pareja, Luis Alfonso [UNESP] (My University, 2009)
Reliability is a key aspect in power system design and planning. Maintaining a reliable power system is a very important issue for their design and operation. Under the new competitive framework of the electricity sector, power systems find ever more and more strained to operate near their limits. Under this new scenario, it is crucial for the system operator to use tools that facilitate an energy dispatch that minimizes possible power cuts. This paper presents a mathematical model to calculate an energy dispatch that considers security constraints (single contingencies in transmission lines and transformers). The model involves pool markets and fixed bilateral contracts. Traditional methodologies that include security constraints are usually based in multistage dispatch processes. In this case, we propose a single-stage model that avoids the economic inefficiencies which result when conventional multi-stage dispatch approaches are applied. The proposed model includes an AC representation of the transport system and allows calculating the cost overruns incurred in due to reliability restrictions. We found that complying with fixed bilateral contracts, when they go above certain levels, might lead to congestion problems in transmission lines.
AC model for the combined dispatch of bilateral contracts and energy pool considering security constraints
Keywords: Electric power systems-protection; Energy markets; Bilateral contracts; Congestion problem; Cost overruns; Design and operations; Electricity sector; Multi-stage; Pool markets; Power cuts; Power system designs; Power systems; Security constraint; Single stage; System operator; Traditional methodologies; Transmission line; Transport systems; Commerce; Electric equipment protection; Electric lines; Electric power measurement; Mathematical models; Mathematical operators; Network security; Traffic congestion; Transmission line theory; Electric power system protection